Analisa Yuridis Praktik Penggunaan Electric Informed Consent di Rumah Sakit Indonesia - Wibowo Pujiarno (Majelis: Jurnal Hukum Indonesia, 2024)
In line with its development, Electronic Medical Records have become the heart of information in the Hospital Management Information System (SIMRS), which is the main application in a basic data management system that collects various sources of medical data, plus other features such as administration, billing and documentation services. medical. However, electronic medical records certainly raise new problems in the area of ​​patient confidentiality and privacy. If a patient's medical data falls into the hands of an unauthorized person, legal problems and responsibilities could arise for the hospital and doctor who handles the patient, therefore standards for making and storing medical records that have been made conventionally or on paper must also be applied to Electronic medical records must be made secure and patient data must be strictly guarded by the hospital, meaning that no information can be opened without the patient's permission, which means that all patient medical information data can only be accessed by interested people. These people are also not allowed to transfer this information to other people. The implementation of Electronic Medical Records in Health Facilities is carried out by a separate work unit or adjusted to the needs and capabilities of each Health Fascily. In terms of the scale of health services, health facilities are very different from hospitals, especially those in remote areas. In fact, not all hospitals are ready to implement a medical history recording system, the total use of telemedicine applications which has increased up to six times during the 2022 COVID-19 pandemic in Indonesia.